VD_FINDINFO Jug / 2011 / 12 vom 10. Dezember 2010 - VD Tribunal cantonal (2010)
DIVORCE, PRÉVOYANCE PROFESSIONNELLE, PARTAGESENS GÉNÉRAL | 122 al. 1 CC, 122 CC, 123 CC, 142 CC, 22 LFLP, 25a al. 1 LFLP, 25a LFLP, 73 al. 1 LPP, 7 OLP, 8a OLP, 12 OPP2